Urgensi dan Mekanisme Biosintesis Metabolit Sekunder Mikroba Laut - Nofiani, Risa (Jurnal Natur Indonesia, 2008)
Marine microorganism is one of biologically active potential resources of secondary metabolites. Its potency areso promising that the knowledge of how its secondary metabolite occured need to be studied and collected. Thoseknowledges will enable further study is improving secondary metabolite production in the laboratory. In nature,secondary metabolites synthesis occur when there are effect of both biotic and abiotic factors such as sea waterand microbe symbiosis with other living materials. When this is explained in metabolic pathways, secondarymetabolite synthesis affected by available nutrient and regulated by autoinducer molecules through quorum sensingmechanism